Outdoor Insulation and Gas Insulated Switchgears - Fofana, Ph.D. ing. Chairholder; Brettschneider, Stephan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on theoretical and practical developments in the performance of high-voltage transmission line against atmospheric pollution and icing. Modifications using suitable fillers are also pinpointed to improve silicone rubber insulation materials. Very fast transient overvoltage (VFTO) mitigation techniques, along with some suggestions for reliable partial discharge measurements under DC voltage stresses inside gas-insulated switchgears, are addressed. The application of an inductor-based filter for the protective performance of surge arresters against indirect lightning strikes is also discussed.